Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L’art autochtone à l’aune du discours critique dans les revues spécialisées en arts visuels au Canada. Les cas de Sakah à n et de Beat Nation - Pageot, Edith-Anne (Muséologies, 2018)
This article offers a qualitative and quantitive analysis of the critical reception of two exhibitions, Sakahàn:International Indigenous Art (National Gallery of Canada, Ottawa 2013) and Beat Nation: Art, Hip-Hop and Aboriginial Culture (organised and circulated by the Vancouver Art Gallery, 2013-2014). The study treats articles which appeared between 2012 and 2015 in English and French visual-arts publications. The comparative analysis intends to highlight general trends, in order to identify challenges that contemporary Indigenous arts pose for art criticism. A review of the texts shows that all commentators, whether francophone or anglophone, indigenous or non-Indigenous, have welcomed these two exhibitions warmly. The discrepancy between the number of essays in French and those in English reflects the demographic weight of these two linguistic communities and the geographic distribution of First Nations in Canada. This will qualify, without denying, the hypothesis of Quebec's tardiness on the indigenous question. The authors largely recognize the necessity of initiating indigenization of the museum and emphasize the movement to internationalize contemporary indigenous art. Yet many commentators, particulary Indigenous people, dispute the efficacity of the concept of "strategic essentialism" put forward by the commissioners of the Sakahàn catalog. Despite both a real interest in these two major exhibitions and the quality of the commentary, in the end, for events of such a scale few texts have been published on the subject. The criteria for appreciation rooted in the institutional sociology of art endeavour to fully take into account the challenges posed by certain central aspects of the approach of several Indigenous creators, such as the intangible dimensions of their civic engagement, the dissolution of particular outside venues and the sisterhood of certain projects.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Figure de l’indiscipline. Domingo Cisneros, un parcours artistique atypique - Pageot, Edith-Anne (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Between 1974 et 1996, the Canadian artist of Mexican origin Domingo Cisneros was seen as a leading figure in contemporary art in Canada. He played a major role in the process of self-determination that First Nations artists undertook following the infamous 1969 White Paper, the Statement of the Government of Canada on Indian Policy. Cisneros was recognized both in the Native and Quebec francophone contemporary art worlds, and was internationally acclaimed within the conceptual and contextual art milieu gathered around the Polish artist Jan Swidzinski. His contribution has nevertheless been forgotten. Coinciding with his seventy-fifth birthday, this article aims to review, conceptually frame, and contextualize Cisneros’s role and impact on the Canadian art scene. It argues that his interdisciplinarity, or “indiscipline,” was instrumental in building connexions and bridges between heterogeneous values, cultural protocols, and epistemological principles.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Présences, mémoires individuelles et plurielles comme dispositifs de construction dans le travail des créatrices autochtones - Pageot, Édith-Anne (Espace, 2018)
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Postcolonial Territorial Landmarks within Canada’s Multiculturalism: The Myth of Virility. - Pageot, Edith-Anne (Landscapes and Landmarks of Canada: Real, Imagined (Re)Viewed, 2017)
Résumé livre : The image of the “land” is an ongoing trope in conceptions of Canada—from the national anthem and the flag to the symbols on coins—the land and nature remain linked to the Canadian sense of belonging and to the image of the nation abroad. Linguistic landscapes reflect the multi-faceted identities and cultural richness of the nations. Earlier portrayals of the land focused on unspoiled landscape, depicted in the paintings of the Group of Seven, for example. Contemporary notions of identity, belonging, and citizenship are established, contested, and legitimized within sites and institutions of public culture, heritage, and representation that reflect integration with the land, transforming landscape into landmarks. The Highway of Heroes originating at Canadian Forces Base Trenton in Ontario and Grosse Île and the Irish Memorial National Historic Site in Québec are examples of landmarks that transform landscape into a built environment that endeavours to respect the land while using it as a site to commemorate, celebrate, and promote Canadian identity. Similarly in literature and the arts, the creation of the built environment and the interaction among those who share it is a recurrent theme. This collection includes essays by Canadian and international scholars whose engagement with the theme stems from their disciplinary perspectives as well as from their personal and professional experience—rooted, at least partially, in their own sense of national identity and in their relationship to Canada.
Keywords: 1-Histoire de l'art; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé